Analisis Pengaruh Mata Kuliah Kewirausahaan dan Motivasi Kewirausahaan Terhadap Minat Untuk Menjadi Pengusaha Muda Islami (Young Entrepreneur) - Bunga Mawar; Zuhrinal M. Nawawi (Cakrawala Repositori IMWI, 2023)
A college or university is an institution that develops its graduates into smart, creative, and independent individuals with quality soft and hard skills. Universities must be able to produce students who are adventurous and entrepreneurial. Students' low interest in entrepreneurship stems from their belief that being an employee is better than being an entrepreneur. Similarly, students are more willing to seek information about job vacancies and are ready to follow the selection process for new employees in government agencies and private companies, rather than preparing themselves to create jobs and work through entrepreneurship. With the growth and development of entrepreneurship science, it will increase the enthusiasm of the Indonesian people, especially the younger generation or students to participate in entrepreneurship and create jobs, not just as job seekers. Entrepreneurship is a major issue in developing countries. The progress or decline of a country's economy is highly dependent on the existence and role of the entrepreneurial group.